Metastatic melanoma to the ovary in pregnancy: A case report - D.S. Huang (Elsevier, 2021)
Metastatic melanoma to the ovary is an uncommon presentation. We report a case of metastatic melanoma to the ovary that presented as a growing left adnexal mass during pregnancy and was thought to be benign by imaging and frozen section pathology. Here we discuss the challenges in radiologic and pathologic diagnosis, as well as considerations for the mother and newborn.